Affine Modules and the Drinfeld Center - Das, Paramita; Ghosh, Shamindra Kumar; Gupta, Ved Prakash (MATHEMATICA SCANDINAVICA, 2016)
Given a finite index subfactor, we show that the affine morphisms at zero level in the affine category over the planar algebra associated to the subfactor is isomorphic to the fusion algebra of the subfactor as a *-algebra. This identification paves the way to analyze the structure of affine P-modules with weight zero for any subfactor planar algebra P (possibly having infinite depth). Further, for irreducible depth two subfactor planar algebras, we establish an additive equivalence between the category of affine P-modules and the center of the category of N-N-bimodules generated by L^2(M); this partially verifies a conjecture of Jones and Walker.